1970
DOI: 10.1103/physreva.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Absolute Cross Sections for (e,H2) Collision Processes. Formation and Decay ofH

Abstract: Energy and angular&dependences of the elastic and inelastic scattering of electrons from H2 have been measured in the energy range 10 to 16 eV and for scattering angles ranging from 10' to 120'. Three resonance series have been investigated starting at 11.30, ll. 50, and 13.63 eV, respectively. The last two series decay preferentially into one single electronic channel, while the first resonance (resonance I) decays into all energetically possible exit channels, i.e. , X'Z~, b Z'", B'Z'". Throughout, stress is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…However, very little information is available for the 14 eV process as compared to that for the 4 eV and 10 eV processes. Transmission as well as scattering experiments had indicated the presence of a 2 Σ g + NIR in the 11eV to 13.5 eV range [20,21]. The same NIR was identified in the electron scattering experiments at 14 eV with a width of 90 meV [21].…”
Section: Coherently Controlled Interaction With Photons Is Known To Isupporting
confidence: 58%
See 1 more Smart Citation
“…However, very little information is available for the 14 eV process as compared to that for the 4 eV and 10 eV processes. Transmission as well as scattering experiments had indicated the presence of a 2 Σ g + NIR in the 11eV to 13.5 eV range [20,21]. The same NIR was identified in the electron scattering experiments at 14 eV with a width of 90 meV [21].…”
Section: Coherently Controlled Interaction With Photons Is Known To Isupporting
confidence: 58%
“…Transmission as well as scattering experiments had indicated the presence of a 2 Σ g + NIR in the 11eV to 13.5 eV range [20,21]. The same NIR was identified in the electron scattering experiments at 14 eV with a width of 90 meV [21]. Subsequent DA measurements concluded that this Σ g + NIR is the main contributor to the 14 eV DA process [22] and this has been the accepted wisdom until now [16,23].…”
Section: Coherently Controlled Interaction With Photons Is Known To Imentioning
confidence: 66%
“…Weingartshofer et al [6], Watson and Anderson [7], Srivastava and Jansen [8], Hall and Andric [9], Ajello et al [10], Nishimura and Danjo [11], Mason and Newell [12], Khakoo and Trajmar [13][14][15], Khakoo and Segura [16] and, more recently, by Wrkich et al [17].…”
Section: Introductionmentioning
confidence: 98%
“…Prior to the Trajmar et al review there was only one study of absolute excitation cross sections for this state, by Weingartshofer et al (1970) and these values have been tabulated by They measured DCS at four energies, 10.5, 11.0, 11.6 and 12.0 eV and also derived integral cross sections at each of these energies. Unfortunately, they do not provide tabulated cross sections.…”
mentioning
confidence: 99%